Negative electrode active material, secondary battery and electric equipment
By introducing a combination of carbon matrix, metal sulfide and non-metal vanadium shell with pores into the negative electrode active material of the battery, the problem of poor cycling performance of the battery at high magnification is solved, and high energy density and fast charging capabilities are achieved and the effect of extending cycle life.
Patent Information
- Application Number
- CN202411551209.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
How to improve the battery's energy density and fast charging capabilities while improving the battery's cycling performance at high magnifications, and solve the problem of negative electrode potential and sodium extraction caused by increased charging rate.
A negative electrode active material is used, which includes a carbon matrix having pores, a metal sulfide distributed in the pores of the carbon matrix, and a non-metallic vanadium shell distributed on the surface of the carbon matrix. By adjusting the compositional proportion and structural characteristics of the material, the specific capacity, energy density and cycling performance of the material are improved.
It realizes the high energy density and fast charging capability of the battery, while extending the cycle life of the battery and slowing down the speed of battery capacity attenuation under fast charging.
Smart Images

Figure BDA0005115485420000101 
Figure BDA0005115485420000111 
Figure BDA0005115485420000112
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode active material, a secondary battery and an electrical device. Background Art
[0002] With the increasing popularity of new energy vehicles, researchers have continued to invest in battery energy density, and battery energy density has made significant progress, which can better meet people's needs for the range of new energy vehicles. However, the long charging time of new energy vehicles has become a current pain point and has received widespread attention from the industry. Increasing energy density and fast charging capabilities are the key to eliminating mileage anxiety and promoting electric vehicles. The development of fast-charging sodium-ion batteries is imminent. Energy density, fast charging capability, and cycle life influence and are interrelated. An increase in the charging rate leads to a lower negative electrode potential, which starts sodium precipitation earlier and causes rapid decay of the battery capacity. Cycling high-energy-density batteries at high rates can also lead to sodium precipitation, causing capacity loss.
[0003] Based on this, how to improve the battery's energy density and fast charging capability while improving the battery's cycle performance at high rates is a technical problem that researchers in this field urgently need to solve when developing fast-charging batteries. Summary of the invention
[0004] Therefore, the present application provides a negative electrode active material, a secondary battery and an electrical device, the purpose of which is to improve the battery's energy density and fast charging capability while improving the battery's cycle performance at high rates.
[0005] In order to achieve the above object, according to one aspect of the present application, a negative electrode active material is provided, comprising:
[0006] a carbon matrix having pores;
[0007] a metal sulfide at least partially distributed in the pores of the carbon matrix;
[0008] A shell layer is distributed on at least a portion of the surface of the carbon matrix, and the shell layer comprises non-metallic vanadium compound.
[0009] Furthermore, the negative electrode active material satisfies at least one of the following conditions:
[0010] a. The carbon matrix includes one or more of hard carbon and soft carbon;
[0011] b. The non-metallic vanadium compound includes one or more of vanadium selenide and vanadium bromide;
[0012] Furthermore, the negative electrode active material satisfies at least one of the following conditions:
[0013] c. The mass of the metal sulfide accounts for 3.5% to 50% of the mass of the negative electrode active material;
[0014] d. The mass of the carbon matrix accounts for 48% to 95% of the mass of the negative electrode active material;
[0015] e. The mass of the shell layer accounts for 1% to 3% of the mass of the negative electrode active material.
[0016] Furthermore, the metal sulfide includes germanium sulfide (GeS 2 ), antimony sulfide (Sb 2 S 3 )
[0017] Furthermore, the metal sulfide includes germanium sulfide and antimony sulfide, the germanium sulfide accounts for 1.4% to 13% of the mass of the negative electrode active material, and the antimony sulfide accounts for 2% to 38% of the mass of the negative electrode active material.
[0018] Furthermore, the particle size Dv50 of the negative electrode active material is 3 to 8 μm, and the porosity of the negative electrode active material is 5% to 35%.
[0019] Furthermore, the compacted density of the negative electrode active material powder is 1 to 1.2 g / cm 3 .
[0020] Furthermore, the negative electrode active material has an initial discharge specific capacity of 300-500 mAh / g at a current density of 0.04 A / g.
[0021] According to another aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises any one of the negative electrode active materials; and the sheet resistance of the negative electrode plate is 1.0-1.9 mΩ.
[0022] According to another aspect of the present application, there is provided an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0023] The negative electrode active material of the present application, through the combined action of the metal sulfide distributed in the pores of the carbon matrix and the shell layer containing non-metallic vanadium compounds distributed on the surface of the carbon matrix, can have significantly improved specific capacity and energy density, and is beneficial to improving the compaction density of the electrode sheet, while significantly improving the structural stability of the battery, achieving fast charging while also slowing down the battery capacity decay under fast charging and extending the cycle life. DETAILED DESCRIPTION
[0024] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0025] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0026] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0027] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0029] In a typical embodiment of the present application, a negative electrode active material is provided, comprising:
[0030] a carbon matrix having pores;
[0031] a metal sulfide at least partially distributed in the pores of the carbon matrix;
[0032] A shell layer is distributed on at least a portion of the surface of the carbon matrix, and the shell layer comprises non-metallic vanadium compound.
[0033] The negative electrode active material of the present application, through the combined action of the metal sulfide distributed in the pores of the carbon matrix and the shell layer containing non-metallic vanadium compounds distributed on the surface of the carbon matrix, can have significantly improved specific capacity and energy density, and is beneficial to improving the compaction density of the electrode sheet, while significantly improving the structural stability of the battery, achieving fast charging while also slowing down the battery capacity decay under fast charging and extending the cycle life.
[0034] In the present invention, non-metallic vanadium compounds refer to compounds formed by the combination of non-metallic elements and vanadium elements.
[0035] In some preferred embodiments, the carbon matrix includes amorphous carbon, which can be hard carbon or soft carbon. These carbon matrix materials have a low expansion rate when embedded with sodium and are rich in pores, which can well confine metal sulfides in the pores of the carbon matrix and maintain their structural stability during later cycles.
[0036] In some preferred embodiments, the non-metallic vanadium compound comprises one or more of vanadium selenide and vanadium bromide; a shell layer comprising the non-metallic vanadium compound is distributed on at least a portion of the surface of the carbon matrix, thereby optimizing sodium ion conduction and enhancing rate performance.
[0037] In some preferred embodiments, the metal sulfide includes one or more of germanium sulfide and antimony sulfide; wherein, the energy density and specific capacity of the battery formed by the carbon matrix are significantly improved by these metal sulfides, and germanium sulfide and antimony sulfide have high specific capacity and large interlayer spacing, which are helpful for sodium ion storage. The metal sulfide and the carbon matrix synergistically exert the capacity and cycle performance of the negative electrode active material.
[0038] In some preferred embodiments, the mass of the metal sulfide accounts for 3.5% to 50% of the mass of the negative electrode active material; for example, in the negative electrode active material, the mass of the metal sulfide accounts for one or any two of 3.5%, 5%, 10%, 30%, 50%. The above range of metal sulfides can further improve the cycle performance and fast charging performance of the negative electrode active material.
[0039] In some preferred embodiments, the mass of the carbon matrix accounts for 48% to 95% of the mass of the negative electrode active material. For example, in the negative electrode active material, the mass of the carbon matrix accounts for one or any two of 95%, 94%, 88%, 68%, and 48%. The carbon matrix can confine the metal sulfide in its pores and inhibit the expansion of the metal sulfide. The carbon matrix in the above range can absorb the expansion stress of the metal sulfide in the cycle overcharge, reduce the risk of pulverization of the negative electrode active material, and further improve the cycle performance and rate performance of the negative electrode active material.
[0040] In some preferred embodiments, the mass of the shell layer accounts for 1% to 3% of the mass of the negative electrode active material; for example, in the negative electrode active material, the mass of the shell layer accounts for one or any two of 1%, 2%, and 3%. The above range of shell layers can further improve the cycle performance and fast charging performance of the negative electrode active material.
[0041] In some preferred embodiments, the metal sulfide includes germanium sulfide and antimony sulfide, the germanium sulfide accounts for 1.4% to 13% of the mass of the negative electrode active material, and the antimony sulfide accounts for 2% to 38% of the mass of the negative electrode active material. For example, in the negative electrode active material, the mass proportion of germanium sulfide is 1.4%, 2%, 5%, 10%, 13% or any two of the range values; the mass proportion of antimony sulfide is 2%, 3%, 5%, 10%, 20%, 30%, 38% or any two of the range values. The above range of germanium sulfide and antimony sulfide can further improve the cycle performance of the negative electrode active material.
[0042] In some preferred embodiments, the particle size Dv50 of the negative electrode active material is 3 to 8 μm, and the porosity of the negative electrode active material is 5% to 35%. For example, D50 can be 3 μm, 5 μm, 8 μm, or any two of them. The porosity can be 5%, 15%, 25%, 35%, or any two of them. The particle size Dv50 and porosity of the negative electrode active material in the above range are conducive to ensuring sufficient metal sulfide distribution in the pores while improving the compaction of the pole piece, and are also conducive to realizing the insertion and extraction of ions in the material under high current density, thereby improving the fast charging performance and cycle performance of the battery.
[0043] In some preferred embodiments, the compacted density of the negative electrode active material powder is 1 to 1.2 g / cm 3 , for example, it can be 1.0 g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 The compaction density of the negative electrode active material is controlled within this range, so that the capacity and energy density of the negative electrode active material can be better improved.
[0044] In some preferred embodiments, the negative electrode active material has an initial discharge specific capacity of 300-500 mAh / g at a current density of 0.04 A / g. For example, the initial discharge specific capacity may be 300 mAh / g, 360 mAh / g, 380 mAh / g, 420 mAh / g, 460 mAh / g, or 500 mAh / g. This indicates that the negative electrode active material has a higher specific capacity, which is beneficial to improving the battery capacity.
[0045] In some preferred embodiments, the method for preparing the negative electrode active material comprises the following steps:
[0046] Step S1: preparing a carbon matrix;
[0047] Step S2: dissolving a metal salt and a sulfur source in an organic solvent to obtain a mixed solution, mixing the mixed solution with a carbon matrix, reacting, taking out a precipitate, drying it, and heat treating it to obtain a product, a carbon matrix loaded with metal sulfide;
[0048] Step S3: The product obtained in S2 is placed in an oleylamine solvent and stirred, and mixed with a vanadium-containing solvent and a mixed solution containing a non-metallic element or a non-metallic salt, and a shell layer containing a non-metallic vanadium compound is generated through a thermal reaction, and then washed to obtain a negative electrode active material.
[0049] In some embodiments of the present application, in step S1, the carbon matrix can be commercially available or homemade. For example, biomass is used as a raw material, reacted with a pore-forming agent, dried, and heat-treated to obtain a carbon matrix. The pore-forming agent can be at least one of sodium hydroxide, potassium hydroxide, potassium permanganate, and sodium permanganate. The mass ratio of biomass to pore-forming agent is 1 to 5:1, for example, 1:1, 3:1, and 5:1. The reaction temperature is 40 to 80°C, further at 40 to 60°C and 45 to 55°C. The reaction time is 5 to 8h. The temperature of the heat treatment is 800 to 1000°C, further at 800 to 950°C and 850 to 950°C. The heat treatment time is 4 to 10h, further at 4 to 8h and 5-8h. The heating rate of the heat treatment is 1 to 10°C / min, further at 1 to 6°C / min and 3 to 6°C / min.
[0050] In some embodiments of the present application, in step S2, the metal salt may be at least one of germanium chloride, antimony chloride, germanium nitrate, antimony nitrate, germanium sulfate, and antimony sulfate. The organic solvent may be at least one of ethylene glycol, ethanol, methanol, and acetone. The sulfur source may be thiourea. The ratio of the molar amount of sulfur element in the sulfur source to the metal element in the metal salt is greater than or equal to 1, and further, between 1 and 5, 1.5 and 2.5. The reaction temperature is 120 to 180°C, and further at 120°C, 160°C, 150°C, and 170°C. The reaction time is 10h, 12h, 14h, and 16h. The temperature of the heat treatment is 300 to 500°C, and further at 300°C, 400°C, 450°C, and 500°C. The heat treatment time is 2 to 4h, and further at 2h, 3h, and 4h.
[0051] In a second aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises any one of the negative electrode active materials; and the sheet resistance of the negative electrode plate is 1.0-1.9 mΩ.
[0052] In some embodiments, the negative electrode plate includes a current collector and a negative electrode active material layer located on at least one side of the current collector, and the negative electrode active material is disposed on the negative electrode active material layer.
[0053] In some embodiments, the negative electrode active material layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to at least one of acetylene black, carbon black, carbon nanotubes, carbon fibers, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyurethane (PU), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), etc. The current collector includes but is not limited to metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or at least one of the alloy foils of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or at least one of the alloy meshes of the above metals).
[0054] In some embodiments of the present application, the negative electrode active material layer includes 70-99wt% of negative electrode active material, 0.5-15wt% of conductive agent and 0.5-15wt% of binder. Further, the mass fraction of the negative electrode active material in the negative electrode active material layer is 70-85wt%, 75-85wt%, 78-82wt%; the mass fraction of the conductive agent in the negative electrode active material layer is 5-12wt%, 8-12wt%; the mass fraction of the binder in the negative electrode active material layer is 5-2wt%, 8-12wt%.
[0055] In some embodiments of the present application, when the negative electrode active material, the conductive agent and the binder are made into the negative electrode active material layer, they are dispersed in a solvent and then coated on the negative electrode current collector and dried to obtain the negative electrode active material layer. For example, N-methylpyrrolidone (NMP) can be used as the solvent.
[0056] In some embodiments of the present application, the secondary battery further includes a positive electrode sheet, a separator located between the positive electrode sheet and the negative electrode sheet, and an electrolyte.
[0057] In some embodiments of the present application, the positive electrode plate may be a metal sodium plate. The electrolyte may be at least one of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. The diaphragm includes, but is not limited to, a single-layer or multi-layer film of one or more materials selected from polyethylene diaphragms, polypropylene diaphragms, and glass fiber diaphragms.
[0058] According to a third aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned secondary battery.
[0059] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it can include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0060] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application.
[0061] Example 1
[0062] This embodiment provides a negative electrode active material, including a carbon matrix, a metal sulfide and vanadium diselenide, wherein the carbon matrix has pores; the metal sulfide is at least partially distributed in the pores of the carbon matrix; and the vanadium diselenide is distributed on at least a portion of the surface of the carbon matrix. Taking the mass of the negative electrode active material as 100%, the mass of the carbon matrix accounts for 66.63%, the mass of germanium sulfide accounts for 9.10%, the mass of antimony sulfide accounts for 22.63%, and the mass of vanadium diselenide accounts for 1.64%.
[0063] The preparation method of the negative electrode active material is as follows:
[0064] (1) Preparation of skeleton material: 10g of walnut shells were washed and dried for pretreatment, and the walnut shells were crushed into particles with an average particle size of 6 μm. The walnut particles were then stirred with a NaOH solution (concentration of 6 mol / L) at 60°C for 6 h. The mass ratio of walnut particles to NaOH was 2.5:1. After the mixture was evenly mixed, it was dried at 90°C for 14 h, placed in a tubular furnace, and heat treated under an argon protective atmosphere. The material was then washed with distilled water until neutral. After drying, a porous hard carbon material (i.e., skeleton material) was obtained. The heat treatment temperature was 900°C, the treatment time was 6 h, and the heating rate was 5°C / min.
[0065] (2) Add metal sources (antimony chloride and germanium chloride) and thiourea to 90 mL of ethylene glycol to obtain a mixed solution, wherein the molar ratio of germanium chloride to antimony chloride is 1:2, and the molar ratio of the sum of the moles of antimony chloride and germanium chloride to thiourea is 3:5. The total concentration of antimony chloride and germanium chloride in the mixed solution is 33.33 mmol / L. After stirring evenly, add 1 g of the above-mentioned porous hard carbon material and stir for 1 hour. Then, put it into a reactor, react at 160°C for 12 hours, take out the precipitate, cool and dry it, and then heat treat it at 400°C for 3 hours to obtain a modified hard carbon negative electrode material.
[0066] (3) Weigh 6 g of modified hard carbon negative electrode material, put it into a three-necked flask (the capacity of the three-necked flask is 250 mL) containing 150 mL of oleylamine, and then put the three-necked flask into a resistance furnace for heating. Heat it at 120°C for 1 hour and pass inert nitrogen to remove the oxidizing atmosphere to obtain sample A. Then, weigh 166.75 mg of vanadium acetylacetonate and 75.61 mg of selenium powder, put them into 20 mL of oleylamine and stir for 3 hours to obtain sample B. Under a protective atmosphere, add sample B dropwise to sample A for reaction for 2 hours, then heat to 160°C for reaction for 1 hour, terminate the reaction, wash repeatedly and dry to obtain a sample coated with VSe. 2 , and deposited with germanium sulfide (GeS 2 ) and antimony sulfide (Sb 2 S 3 ) of hard carbon materials.
[0067] This embodiment also provides a lithium ion secondary battery, and the preparation method thereof is as follows:
[0068] (1) Preparation of negative electrode sheet
[0069] The negative electrode active material, acetylene black and polyvinylidene fluoride prepared above were mixed in a mass ratio of 7:2:1, ground and mixed evenly, and then an appropriate amount of N-methylpyrrolidone (NMP) was added to prepare an electrode slurry, which was then scraped onto one side of a copper foil, vacuum dried at 80°C for 12 hours, and then rolled and punched into small discs with a diameter of 12 mm.
[0070] (2) Assembling the battery
[0071] In a glove box with a water and oxygen content lower than 0.1 ppm, button cells were assembled using a 7 μm glass fiber separator, a sodium hexafluorophosphate electrolyte (a mixture of ethylene carbonate and diethyl carbonate containing 1 M sodium hexafluorophosphate (the volume ratio of ethylene carbonate and diethyl carbonate was 1:1) containing 5% fluoroethylene carbonate), and a metal sodium sheet as a counter electrode.
[0072] Embodiment 2-3
[0073] The preparation process is the same as that of Example 1, except that the type of the metal source in step (2) during the preparation of the negative electrode active material is adjusted.
[0074] Embodiment 4-5
[0075] The preparation process is the same as that of Example 1, except that the molar ratio of antimony chloride and germanium chloride in the mixed solution in step (2) and the mass of the hard carbon material in the preparation process of the negative electrode active material are adjusted to prepare negative electrode active materials with different carbon matrix, germanium sulfide and antimony sulfide contents.
[0076] Embodiment 6-7
[0077] The preparation process is the same as that of Example 1, except that the amount of vanadium acetylacetonate and selenium powder added in step (3) of the negative electrode active material preparation process is adjusted to prepare negative electrode active materials with different vanadium diselenide mass contents.
[0078] Example 8
[0079] The preparation process is the same as that of Example 1, except that the selenium powder is replaced with ammonium bromide in step (3) of the preparation process of the negative electrode active material to prepare a negative electrode active material with vanadium tribromide as the shell material.
[0080] Examples 9 to 12
[0081] The preparation process is the same as that of Example 1, except that the calcination temperature (800-1600°C), time (3-48h) and heating rate (3-10°C / min) in step (1) of the negative electrode active material preparation process are adjusted to obtain negative electrode active materials with different Dv50 and powder compaction density.
[0082] Embodiment 13
[0083] The preparation process is the same as that of Example 1, except that in step 1, walnut shells are replaced with asphalt to prepare soft carbon as the skeleton material.
[0084] Comparative Example 1
[0085] The preparation process is the same as that of Example 1, except that step (3) is not performed during the preparation of the negative electrode active material, that is, the obtained negative electrode active material has no shell layer.
[0086] Comparative Example 2
[0087] The preparation process is the same as that of Example 1, except that step (2) is not performed during the preparation of the negative electrode active material, that is, the negative electrode active material is obtained without metal sulfide.
[0088] The test methods for relevant characteristics and performance are as follows:
[0089] 1. Determination of physical parameters
[0090] (1) Particle size distribution determination: The particle size was measured using a laser particle size analyzer, wherein the test parameters were: opacity (8-12%), agitator / pump speed (2300 rpm), dispersant (1% ethylphenyl polyethylene glycol), refractive index (2.42), external ultrasound and power (53 kHz, 3 min).
[0091] (2) Porosity determination: The porosity of the material was tested using a fully automatic static volumetric specific surface area and porosity analyzer.
[0092] (3) Determination of compaction density: Mold: The diameter of the gasket is 13 mm, the diameter of the top column is 13 mm, and the inner diameter of the metal cylindrical sleeve is 13 mm. Test conditions: weigh 1 g of negative electrode material, pressurization speed: 1 mm / min, pressure points: 3, 10, 15, 20 kN (continuous pressurization), pressurization and holding time: 30 s, and the test result of 20 kN is the compaction density.
[0093] 2. Diaphragm resistivity determination: The two-probe method is used to characterize the overall penetration internal resistance of the diaphragm. The electrode sheet is cut into a pole piece with a diameter of 14 mm, and a pressure of 25 MPa is applied for a holding time of 25 s.
[0094] 3. First discharge specific capacity: Charge and discharge the button battery at a current density of 0.04A / g, and the capacity obtained is the first discharge specific capacity;
[0095] 4. Determination of rate discharge performance: ratio of discharge capacity obtained at current density 1A / g to that at 0.04A / g.
[0096] 5. Cycle performance measurement: voltage test range 0.005 ~ 2V, cycle test current is 1A / g.
[0097] Table 1
[0098]
[0099]
[0100] Table 2
[0101]
[0102] According to the above data, when the negative electrode active material includes metal sulfides distributed in the pores of the carbon matrix and a shell layer containing non-metallic vanadium compounds distributed on the surface of the carbon matrix, the battery has a higher energy density and better cycle performance. While achieving fast charging, it can also slow down the battery capacity attenuation under fast charging and extend the cycle life.
[0103] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A negative electrode active material, characterized in that: include: a carbon matrix having pores; a metal sulfide at least partially distributed in the pores of the carbon matrix; A shell layer is distributed on at least a portion of the surface of the carbon matrix, and the shell layer comprises non-metallic vanadium compound.
2. The negative electrode active material according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions: a. The carbon matrix includes one or more of hard carbon and soft carbon; b. The non-metallic vanadium compound includes one or more of vanadium selenide and vanadium bromide; c. The mass of the metal sulfide accounts for 3.5% to 50% of the mass of the negative electrode active material; d. The mass of the carbon matrix accounts for 48% to 95% of the mass of the negative electrode active material; e. The mass of the shell layer accounts for 1% to 3% of the mass of the negative electrode active material.
3. The negative electrode active material according to claim 1, characterized in that The metal sulfide includes one or more of germanium sulfide and antimony sulfide.
4. The negative electrode active material according to claim 3, characterized in that The metal sulfide comprises germanium sulfide and antimony sulfide, the germanium sulfide accounts for 1.4% to 13% of the mass of the negative electrode active material, and the antimony sulfide accounts for 2% to 38% of the mass of the negative electrode active material.
5. The negative electrode active material according to claim 1, characterized in that The particle size Dv50 of the negative electrode active material is 3 to 8 μm, and the porosity of the negative electrode active material is 5% to 35%.
6. The negative electrode active material according to claim 1, characterized in that The powder compaction density of the negative electrode active material is 1 to 1.2 g / cm 3 .
7. The negative electrode active material according to claim 1, characterized in that The negative electrode active material has a first discharge specific capacity of 300-500 mAh / g at a current density of 0.04 A / g.
8. A secondary battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode active material according to any one of claims 1 to 7; and the film resistance of the negative electrode plate is 1.0-1.9 mΩ.
9. An electrical device, characterized in that: The secondary battery according to claim 8 is included, and the secondary battery is used as a power supply for the electrical device.